Exploring the Causes, Consequences, and Control Strategies of Corruption: Youths’ Perceptions in the Context of Nepal - Khadka, Arjun Kumar (Rural Development Journal, 2026)
Corruption is deeply rooted in Nepal, undermining governance, economic development, and social justice. Although legal frameworks exist, enforcement remains weak. Youth, representing nearly 40% of the population, are particularly vulnerable to the effects of corruption and possess a critical role in anti-corruption efforts. This study aims to: Identify key causes of corruption as perceived by Nepali youth; Examine its most damaging societal and governance consequences; Evaluate the effectiveness of current anti-corruption measures; and Explore alternative strategies for corruption control. A descriptive survey approach was used, collecting data from 398 youth in the Kathmandu Valley through stratified random sampling. A structured Likert-scale questionnaire assessed perceptions of causes, consequences, and anti-corruption mechanisms. Analyses included descriptive statistics, chi-square tests, ANOVA, and correlation analysis to determine significant patterns and subgroup differences. Top perceived causes included greed for money (mean = 4.32), the political-bureaucratic nexus (mean = 4.25), and weak property rights (mean = 4.18) on a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree). Major consequences were increased inequality (mean = 4.62) and societal distrust (mean = 4.55). Current mechanisms such as the CIAA were deemed ineffective (mean = 2.1), with whistleblower protection scoring lowest (mean = 1.7), indicating low perceived effectiveness. Youth proposed stronger whistleblower laws (42%), youth-led monitoring (38%), and digital transparency platforms (33%). The findings emphasize the urgent need for systemic reforms, active youth engagement, and innovative digital solutions. Tackling financial greed, political collusion, and weak institutions is vital to restore trust and foster transparency in Nepal.